2019
DOI: 10.1017/s0144686x19000576
|View full text |Cite
|
Sign up to set email alerts
|

Understanding dementia in ethnically diverse groups: a qualitative study from Norway

Abstract: As the number of older immigrants in Europe rises, dementia within minority ethnic populations warrants attention as a significant public health problem. Equitable health and care services constitute a prioritised health policy aim on both supranational and national levels in Europe and is formulated in the Norwegian health legislation. Through interviews and focus groups with older immigrants, relatives of immigrants with dementia and health personnel, we explored the perceptions of dementia among ethnically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Fourteen studies contributed to this theme (Berdai Chaouni & De Donder, 2019; Czapka & Sagbakken, 2020; Hossain & Khan, 2019; Liu et al, 2020; McCleary et al, 2013; Morhardt et al, 2010; Naess & Moen, 2015; Nielsen et al, 2020; Ramsay et al, 2017; Sagbakken et al, 2020; Sun et al, 2014; van Wezel et al, 2018; Xiao et al, 2015; Yeo et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourteen studies contributed to this theme (Berdai Chaouni & De Donder, 2019; Czapka & Sagbakken, 2020; Hossain & Khan, 2019; Liu et al, 2020; McCleary et al, 2013; Morhardt et al, 2010; Naess & Moen, 2015; Nielsen et al, 2020; Ramsay et al, 2017; Sagbakken et al, 2020; Sun et al, 2014; van Wezel et al, 2018; Xiao et al, 2015; Yeo et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies contributed to this theme (Ahmad et al, 2020; Berdai Chaouni et al, 2020; Berdai Chaouni & De Donder, 2019; Caldwell et al, 2014; Czapka & Sagbakken, 2020; Jutlla, 2015; Kong et al, 2010; Monsees et al, 2020; Morhardt et al, 2010; Naess & Moen, 2015; Nielsen et al, 2020; Ramsay et al, 2017; Sagbakken et al, 2017, 2020; Sun et al, 2014; van Wezel et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research project has already published 3 papers; one paper explored the perceptions of dementia and cognitive impairment among healthy older immigrants and relatives of immigrants with dementia [29]; another paper explored the experiences of health personnel with regard to identifying, assessing and diagnosing immigrants with dementia [30], while the third paper focused on different care patterns among immigrant groups [31].…”
Section: Methodsmentioning
confidence: 99%
“…These reflections may therefore assume a special relevance in migrants and subjects composing minority groups. In fact, it has been shown that these individuals may have different attitudes toward mental and cognitive disturbances [7,8] and frequently have delayed contact with dedicated healthcare and social services [9]. Moreover, in Western countries, there is still a paucity and a scarce adoption of instruments and tools supporting a culture-sensitive (and, thus, more reliable) evaluation of cognitive performance [10,11].…”
Section: Introductionmentioning
confidence: 99%